Development of climate zones for passive cooling techniques in the hot and humid climate of Indonesia. (December 2022) - Putra, I Dewa Gede Arya; Nimiya, Hideyo; Sopaheluwakan, Ardhasena; Kubota, Tetsu; Lee, Han Soo; Pradana, Radyan Putra; Alfata, Muhammad Nur Fajri; Perdana, Reza Bayu; Permana, Donaldi Sukma; Riama, Nelly Florida
Abstract: The classification of climate zones is required for developing appropriate predesign strategies for energy-efficient buildings. Standardized hourly climatic data from 2014 to 2020, including global horizontal irradiance, air temperature, wind speed, relative humidity, precipitation, atmospheric pressure, total cloud cover, and mixing ratio, collected from 106 sites were used for climate zoning in Indonesia. First, the temperature zones containing four area divisions were determined to obtain statistical patterns of diurnal and seasonal air temperature. The comfort ventilation potential was assessed based on a zoning using a combination of air temperature and wind speed characteristics, while the evaporative cooling potential was assessed based on the combination of relative humidity and wind speed characteristics. Total hours for comfort ventilation and evaporative cooling showed diurnal (daytime and nighttime) and seasonal changes. Second, eight integrated climate zones namely, equatorial, sub-equatorial, highland tropical, very highland tropical, monsoonal, sub-monsoonal, savanna, and sub-savanna, were determined based on principal component analysis, cluster analysis, and spatial interpolation methods. Third, the calculation of cooling degree days and cooling loads followed by the calculation of the potentials for night ventilation, comfort ventilation, and evaporative cooling were carried out in each integrated climate zone. For example, by taking the lower probability limit of 50%, the monsoonal, savanna, and sub-savanna climate zones were found to be suitable for comfort ventilation methods. Meanwhile, the sub-equatorial climate zone was suitable for applying passive methods by combining night ventilation and comfort ventilation. Highlights: Hourly climatic data of eight factors were used for climate zoning. Development system of climate zones for passive cooling techniques was proposed. The novel integrated climate zoning with eight zones was developed for Indonesia. Potentials of three passive cooling methods were assessed in each climate zone.